Differing Perceptions of Advanced Driver Assistance Systems (ADAS). (September 2016) - Crump, Caroline; Cades, David; Lester, Benjamin; Reed, Scott; Barakat, Brandon; Milan, Laurene; Young, Douglas
The extent to which drivers' attitudes toward the use of autonomous vehicle systems can be influenced by various driver factors (e.g., driver age, experience with the systems, etc.) has yet to be firmly established. To investigate driver perceptions and acceptance of advanced vehicle systems, the current research examined initial and repeated exposure to systems while driving under various commonly encountered on-road situations (e.g., emergency braking). Somewhat surprisingly, driver perceptions of safety when driving vehicles with assistive technologies diminished following repeated exposure to the technologies. However, when drivers were afforded more extensive experience, they reported a heightened appreciation of the systems—especially drivers who might benefit most from this assistance (e.g., distracted or older drivers).